Join the IDNLearn.com community and start getting the answers you need today. Get prompt and accurate answers to your questions from our experts who are always ready to help.

Here is the formatted and corrected version of the question:

-----

The following table shows the function [tex]g(x)[/tex].

[tex]\[
\begin{tabular}{|c|c|}
\hline
$x$ & $g(x)$ \\
\hline
-5 & 4 \\
\hline
-4 & 1 \\
\hline
-3 & 0 \\
\hline
-2 & 1 \\
\hline
\end{tabular}
\][/tex]

Which statement about the functions is true?

A. [tex]f(x)[/tex] and [tex]g(x)[/tex] intersect at exactly one point.

B. [tex]f(x)[/tex] is greater than [tex]g(x)[/tex] for all values of [tex]x[/tex].

-----


Sagot :

To analyze the functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] based on the given values, let's break down the steps:

1. Given Data:
- The table provides the values for [tex]\( g(x) \)[/tex] at specific points:
[tex]\[ \begin{array}{|c|c|} \hline x & g(x) \\ \hline -5 & 4 \\ -4 & 1 \\ -3 & 0 \\ \hline -2 & 1 \\ \hline \end{array} \][/tex]

2. Assumption about [tex]\( f(x) \)[/tex]:
- Let's assume [tex]\( f(x) \)[/tex] is given by the function [tex]\( f(x) = x + 1 \)[/tex].

3. Calculating [tex]\( f(x) \)[/tex]:
- For [tex]\( x = -5 \)[/tex]:
[tex]\[ f(-5) = -5 + 1 = -4 \][/tex]
- For [tex]\( x = -4 \)[/tex]:
[tex]\[ f(-4) = -4 + 1 = -3 \][/tex]
- For [tex]\( x = -3 \)[/tex]:
[tex]\[ f(-3) = -3 + 1 = -2 \][/tex]
- For [tex]\( x = -2 \)[/tex]:
[tex]\[ f(-2) = -2 + 1 = -1 \][/tex]

Thus, the values for [tex]\( f(x) \)[/tex] at these points are:

[tex]\[ \begin{array}{|c|c|} \hline x & f(x) \\ \hline -5 & -4 \\ -4 & -3 \\ -3 & -2 \\ \hline -2 & -1 \\ \hline \end{array} \][/tex]

4. Comparing [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex]:
- At [tex]\( x = -5 \)[/tex]:
[tex]\[ f(-5) = -4, \quad g(-5) = 4 \][/tex]
- At [tex]\( x = -4 \)[/tex]:
[tex]\[ f(-4) = -3, \quad g(-4) = 1 \][/tex]
- At [tex]\( x = -3 \)[/tex]:
[tex]\[ f(-3) = -2, \quad g(-3) = 0 \][/tex]
- At [tex]\( x = -2 \)[/tex]:
[tex]\[ f(-2) = -1, \quad g(-2) = 1 \][/tex]

5. Checking Intersections:
- The functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] intersect where [tex]\( f(x) = g(x) \)[/tex].
- From the above comparisons, we note that [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] do not intersect at any of these points.
- Therefore, there are no points where they intersect.

6. Checking [tex]\( f(x) \)[/tex] Greater than [tex]\( g(x) \)[/tex]:
- To determine if [tex]\( f(x) \)[/tex] is greater than [tex]\( g(x) \)[/tex] for all given [tex]\( x \)[/tex]:
- At [tex]\( x = -5 \)[/tex]: [tex]\( f(-5) = -4 \)[/tex] and [tex]\( g(-5) = 4 \)[/tex]. Here, [tex]\( f(-5) < g(-5) \)[/tex].
- At [tex]\( x = -4 \)[/tex]: [tex]\( f(-4) = -3 \)[/tex] and [tex]\( g(-4) = 1 \)[/tex]. Here, [tex]\( f(-4) < g(-4) \)[/tex].
- At [tex]\( x = -3 \)[/tex]: [tex]\( f(-3) = -2 \)[/tex] and [tex]\( g(-3) = 0 \)[/tex]. Here, [tex]\( f(-3) < g(-3) \)[/tex].
- At [tex]\( x = -2 \)[/tex]: [tex]\( f(-2) = -1 \)[/tex] and [tex]\( g(-2) = 1 \)[/tex]. Here, [tex]\( f(-2) < g(-2) \)[/tex].
- Hence, [tex]\( f(x) \)[/tex] is not greater than [tex]\( g(x) \)[/tex] for any given [tex]\( x \)[/tex].

Conclusion:
- The statement "f(x) and g(x) intersect at exactly one point" is false.
- The statement "f(x) is greater than g(x) for all values of x" is also false.

Thus, neither statement about the functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] is true.